Process parameters and system responses in friction extrusion. (6th January 2023) - Reza-E-Rabby, Md.; Li, Xiao; Grant, Glenn; Mathaudhu, Suveen; Reynolds, Anthony
Abstract: Friction extrusion is an emerging manufacturing process that imparts improved properties and unique microstructures to materials. In this study, the effects of die features (i.e., the absence or presence of die face scrolling) and process parameters (i.e., die rotational speeds and feed rates) on response variables (e.g., extrusion force, torque, power, and temperature) were investigated. During this work, wires with good integrity and similar geometries were extruded over a range of experimental trials with different rotational speeds and feed rates at a constant extrusion ratio. The extrusion force linearly varies with die advance per revolution, which is the ratio of feed rate and rotational speed. The extrusion energy per kilogram mass of extrudate varies non-linearly and asymptotically such that energy consumption is highest at the lowest feed rate and lowest at the highest feed rate. Relationships among other variables (i.e., die advance per revolution, torque, power heat input, and temperature) also were evaluated to elucidate their interdependences.